Representation of 13th century Javanese local wisdom education in the webcomic series “dedes” by Esti Siwi - Kurniawati, Dwi; Fransisca, Sherly; Sidik, Andri Muamar (EDUCTUM: Journal Research, 2026)
This study aims to reveal the local wisdom education of the 13th-century Javanese society visualized in the images and texts of the webcomic “Dedes” by Esti Siwi in the Webtoon digital comic publication. This research is a qualitative type with content analysis through documentation of works and literature studies. The research method applies Peirce's semiotics. Data are analyzed based on Miles & Huberman's interactive data analysis through the stages of data reduction, data presentation, and conclusion drawing. This study produces a representation of the local wisdom education of the 13th-century Javanese society conveyed through artifacts, sociofacts, and mentifaks in the webcomic “Dedes”, namely (1) local visual skills of Candi Kidal which influence indigenous elements, (2) local knowledge about the virtue of living a life of devotion to parents, (3) local values ??in the form of attitudes towards the requirements of caste rules, and (4) local decision mechanisms of king figures who hold community life. This study produces recommendations for Webtoon comic artists to present the local wisdom of each region as an effort to inherit local wisdom education through the utilization of digital technology developments.